Reduction in adverse environmental impacts associated with the operation of combine harvesters during the harvesting of winter oilseed rape - Špokas, Liudvikas; Steponavičius, Dainius; Žebrauskas, Gediminas; Čiplienė, Aušra; Bauša, Laimis (Journal of Environmental Engineering and Landscape Management, 2019)
When harvesting winter oilseed rape (WOSR), leaving higher (~0.3–0.4 m) crop stubble is an effective method of reducing fuel consumption and contaminant emissions of a combine harvester equipped with the tangential threshing apparatus and straw walkers. At a speed of 4 km h−1, when the stubble height of WOSR was increased from 0.2 to 0.4 m, the mass of material other than grain (MOG) fed to the harvester was reduced by 7 t h−1, resulting in a reduction of 6.2 l h−1 in fuel consumption, 5.7 kg h−1 in carbon equivalent (CE), and 16.3 kg h−1 in CO2 emissions. A more accurate estimate of harvester performance is the fuel consumption per ton of threshed seeds. On increasing the MOG mass feed rate to 15.6 t h−1, the fuel consumption per ton of threshed rapeseeds decreased to 3.33 l t−1, CE reached 40.2 kg h−1 or 3.0 kg t−1, and CO2 emissions reached 121.3 kg h−1 or 9.2 kg t−1 of threshed rapeseed. When optimizing the automatic speed control system of the combine harvester, the MOG mass feed rate, the permissible limit of seed losses, and fuel consumption per ton of threshed seeds must be considered.